2022
DOI: 10.1080/10717544.2022.2104405
|View full text |Cite
|
Sign up to set email alerts
|

Nose to brain delivery of melatonin lipidic nanocapsules as a promising post-ischemic neuroprotective therapeutic modality

Abstract: Ischemic stroke accounts for about 87% of all strokes, causing long-term disability in adults, and is the second leading cause of death worldwide. In search of new therapeutic modalities, the use of neuroprotective agents loaded in nanocarriers to be delivered by noninvasive means (i.e. via intranasal route) became a popular approach. In the current study, melatonin (MEL) was loaded in lipidic nanocapsules (LNCs) prepared using the phase inversion method, and characterized in terms of size, polydispersity, zet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…These drawbacks led the researchers to continuously explore new and effective delivery systems alongside new routes of administration to deliver a therapeutic meaningful concentration to brain. Several studies have reported different innovative nano-platforms for improved oral and intranasal delivery of MLT [ [12] , [13] , [14] , [15] , [16] ]. Among others nanocarriers, lipid-based nanoparticles have been widely investigated for penetrating the intact BBB [ [17] , [18] , [19] ] as well as bypassing the BBB via direct nose-to-brain delivery of various drugs [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks led the researchers to continuously explore new and effective delivery systems alongside new routes of administration to deliver a therapeutic meaningful concentration to brain. Several studies have reported different innovative nano-platforms for improved oral and intranasal delivery of MLT [ [12] , [13] , [14] , [15] , [16] ]. Among others nanocarriers, lipid-based nanoparticles have been widely investigated for penetrating the intact BBB [ [17] , [18] , [19] ] as well as bypassing the BBB via direct nose-to-brain delivery of various drugs [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in a rat model of ischemia/reperfusion injury, another study found that intranasal administration of melatonin loaded in lipidic nanocapsules post-stroke can increase the number of surviving neurons in the hippocampal CA1 region and improve oxidative stress and inflammatory marker levels in the hippocampus. These effects were even more pronounced than those observed with oral melatonin administration [460].…”
Section: Post-stroke Melatonin Treatmentmentioning
confidence: 75%
“…They proved that the prepared drug loaded LNCs have lessened the in vivo glioma growth by about 81% [104]. Also, Bseiso et al concluded that melatonin loaded LNCs may be an encouraging delivery system for nose to brain delivery for the remedy of cerebral ischemia [105]. Successful preparation of melatonin loaded LNCs with suitable physicochemical properties resulted in high ex vivo nasal permeation and promising neuroprotective effects in vivo, suggesting the therapeutic potential of LNCs in lessening the effects of ischemic stroke.…”
Section: Applications Of Lipid Nanocapsules In Nose-to-brain Drug Del...mentioning
confidence: 99%